2008
DOI: 10.1243/09544054jem1134
|View full text |Cite
|
Sign up to set email alerts
|

Optimal machining parameters in the cutting process of glass fibre using the reliability analysis based on the Taguchi method

Abstract: Based on reliability analysis, this paper describes a new approach for optimizing the cutting process using the Taguchi method. This approach uses optimized cutting parameters, such as the cutting speed, the cutting volume, and the cutting load for cutting glass fibres, with the application of the Weibull modulus to the blade wear. The minimum blade wear, using the Taguchi method, was found to be the lowest cutting speed and the medium cutting load. The cutting volume had little effect on blade wear. An analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Yang et al 9 suggested that improvement of yield can be regarded as the most important capability indicator in any current production or management field, as yield improvements represent improvements in performance perception. Traditionally, yield analysis is measured by the Cpk value of the process capability indices, which index refers to evaluation according to the quality capabilities presented, when all known process quality factors are controlled under the normal conditions of three major data, including characteristic value specifications, the central position of the process characteristics, and consistency in the deviation presentation of the process center (process accuracy) and process consistency (process precision).…”
Section: Research Methods and Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al 9 suggested that improvement of yield can be regarded as the most important capability indicator in any current production or management field, as yield improvements represent improvements in performance perception. Traditionally, yield analysis is measured by the Cpk value of the process capability indices, which index refers to evaluation according to the quality capabilities presented, when all known process quality factors are controlled under the normal conditions of three major data, including characteristic value specifications, the central position of the process characteristics, and consistency in the deviation presentation of the process center (process accuracy) and process consistency (process precision).…”
Section: Research Methods and Case Studymentioning
confidence: 99%
“…A practical and convenient process for shaping electrically non-conductive ceramics was developed, with the features of high efficiency, high precision, and excellent surface integrity. Yang et al 9 described a new approach for optimizing the cutting process using the Taguchi method. A comparison with the wear of the Weibull modulus showed that the most optimal cutting parameter is A1B3C3.…”
Section: Introductionmentioning
confidence: 99%
“…In each group, the curves are distinguished from each other by the effect of the feed rate value. Based on a reliability analysis, and using the Taguchi method, Yang et al 20 indicated that the cutting speed is the most significant parameter in the cutting process. Their finding is conforming to what was found in this article.…”
Section: Model Validationmentioning
confidence: 99%
“…Closer to the structure of the carbon fibers, a number of severing trials were performed on 66 tex E-glass fibers. 17,18 By relying on statistical Taguchi methods, the authors determined the optimal cutting conditions (i.e. cutting speed, volume, and force capable) to minimize the wear on the high-carbon steel thin blade disk cutters used in experiments.…”
Section: Introductionmentioning
confidence: 99%